Validation of the Questionnaire on Sexual and Reproductive Health Literacy for Adolescents Age 15 to 19 Years in Lao People's Democratic Republic - Viengnakhone Vongxay; Souksamone Thongmixay; Lianne Stoltenborg; Amphone Inthapanyo; Vanphanom Sychareun; Kongmany Chaleunvong; Dirk Rombout Essink (SLACK Incorporated, 2022)
Background: Beyond sexual and reproductive health (SRH) knowledge, it is sexual and reproductive health literacy (SRHL) that reflects the capacity to deal with sexuality. Many interventions have been conducted to increase SRH knowledge in adolescents, but SRHL has rarely been measured, and a well-validated tool is needed to measure it. Objective: This study aimed to validate a tool to measure adolescent SRHL. Methods: Reliability, validity, and cultural equivalence were investigated using data from expert consultations, cognitive interviews, and two-pilot studies. Then adaptation was made to the SRHL questionnaire for correct use among Southeast Asian adolescents in Lao and in wider groups. Key Results: The SRHL tool was comprised of 39 question items focusing on teenage pregnancy, contraception, and abortion. Conceptual, item, and semantic equivalence were all met. Interviewer-administrated mode was found to be optimal. Each question offers the answer choices very difficult, difficult, easy, and very easy, with a good to excellent Cronbach's alpha (0.8-0.9); there were no missing items and no floor/ceiling effects. Construct validity was high as 6 of 7 hypotheses were confirmed. Conclusion: Validation was completed with good cross-cultural validity. The tool was shown to be effective in determining the level of SRHL in adolescents in Laos and potentially in other countries with similar cultures. [HLRP: Health Literacy Research and Practice. 2022;6(1):e37-e50.] Plain Language Summary: To find out how much adolescents know about sexual and reproductive health, an appropriate instrument of measurement is needed. Using different methods, we investigated the performance of a new tool, namely the SRHL questionnaire, which has 39 questions and should be used with an interviewer to assist in recording responses. This new tool could be used effectively to determine the level of literacy on sexual and reproductive health among adolescents.